2022
DOI: 10.1007/s00153-022-00820-y
|View full text |Cite
|
Sign up to set email alerts
|

Weak essentially undecidable theories of concatenation

Abstract: In the language $$\lbrace 0, 1, \circ , \preceq \rbrace $$ { 0 , 1 , ∘ , ⪯ } , where 0 and 1 are constant symbols, $$\circ $$ ∘ is a binary function symbol and $$\preceq $$ ⪯ is a binary relation symbol, we formulate two theories, $$ \textsf {… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…In Ganea [7], Švejdar [22], and Visser [26], it is shown that 𝖳𝖢 is mutually interpretable with 𝖰. In [14], we prove mutual interpretability of 𝖳𝖢 and a fragment whose intended model is the free semigroup of binary strings extended with the prefix relation. The binary operation of pairing is essential for encoding other mathematical objects like tuples and sequences of arbitrary length.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…In Ganea [7], Švejdar [22], and Visser [26], it is shown that 𝖳𝖢 is mutually interpretable with 𝖰. In [14], we prove mutual interpretability of 𝖳𝖢 and a fragment whose intended model is the free semigroup of binary strings extended with the prefix relation. The binary operation of pairing is essential for encoding other mathematical objects like tuples and sequences of arbitrary length.…”
Section: Introductionmentioning
confidence: 91%
“…In Ganea [7], Švejdar [22], and Visser [26], it is shown that TC$\mathsf {TC}$ is mutually interpretable with Q$\mathsf {Q}$. In [14], we prove mutual interpretability of TC$\mathsf {TC}$ and a fragment whose intended model is the free semigroup of binary strings extended with the prefix relation.…”
Section: Introductionmentioning
confidence: 99%
“…One can show that Succ • is decidable and that every sentence is equivalent to a Boolean combination of sentences C n saying 'there is a cycle of size n'. See, e.g., [12,Appendix A]. We note that, over Succ • , the C n are mutually independent.…”
Section: Theorem 42 Every Effectively If-essentially F-incomplete The...mentioning
confidence: 99%
“…⊣ The relationships between these non-effective notions are visualised in Figure 1. In [12], the existence of a decidable f-essentially incomplete theory was proved. Also, essential hereditary undecidability and computable inseparability are incomparable in general (cf.…”
Section: Taishi Kurahashi and Albert Vissermentioning
confidence: 99%
“…These are natural theories given by a handful of transparent axioms. They are all mutually interpretable with each other and also with a number of other natural theories, e.g., the tree theories studied in Kristiansen & Murwanashyaka [9], Damnjanovic [2] [3] and Murwanashyaka [11], and the concatenation theories studied in Murwanashyaka [10].…”
Section: Introductionmentioning
confidence: 99%